Eﬄux in the Oral Metagenome: The Discovery of a Novel Tetracycline and Tigecycline ABC Transporter - Reynolds, Liam J.; Roberts, Adam P.; Anjum, Muna F. (Frontiers in Microbiology, 2016)
Abstract Antibiotic resistance in human bacterial pathogens and commensals is threatening our ability to treat infections and conduct now common medical procedures. As novel antibiotics are discovered and marketed it is important that we understand how resistance to them may arise and know what environments may act as reservoirs for such resistance genes. In this study a tetracycline and tigecycline resistant clone was identified by screening a human saliva metagenomic library in E. coli EPI300 on agar containing 5 μg/ml tetracycline. Sequencing of the DNA insert present within the tetracycline resistant clone revealed it to contain a 7,765 bp fragment harbouring novel ABC half transporter genes, tetAB(60). Mutagenesis studies performed on these genes confirmed that they were responsible for the tetracycline and tigecycline resistance phenotypes. Growth studies performed using E. coli EPI300 clones that harboured either the wild type, the mutated, or none of these genes indicated that there was a fitness cost associated with presence of these genes, with the isolate harbouring both genes exhibiting a significantly slower growth than control strains. Given the emergence of E. coli strains that are sensitive only to tigecycline and doxycycline it is concerning that such a resistance mechanism has been identified in the human oral cavity.